CAD in kidney transplant recipients: a real-world assessment pre-ISCHEMIA-CKD. (3rd October 2022) - Rocha, B; Amador, R; Maltes, S; Cunha, G; Mateus, C; Aguiar, C; Weigert, A; Mendes, M
Abstract: Background: The ISCHEMIA-CKD trial has shown that an initial invasive strategy, as compared to conservative treatment, did not reduce the risk of death and non-fatal myocardial infarction, nor did it improve quality-of-life in patients with advanced chronic kidney disease (CKD) and coronary artery disease (CAD) with moderate-to-severe ischemia. Similar findings were reported in patients with CKD enlisted for kidney transplantation (KT). We aimed to evaluate screening and treatment CAD strategies in patients who ultimately underwent KT at our center. Methods: This is a single-center study of consecutive patients who received a KT from 2015 to 2020. Obstructive CAD was defined whenever one of the following criteria was met: lesion with a stenosis >70% (or >50%, if left main disease) or CAD requiring revascularization, as per the Heart Team discussion. CAD evaluation refers to non-invasive or invasive coronary angiography and/or stress testing, irrespective of clinical scenario. Results: A total of 324 patients underwent KT [mean age 55±12 years; 65.1% male; CKD most often due to hypertensive or diabetic nephropathy and polycystic kidney disease – 41.8%; median time from renal replacement therapy (RRT) to KT – 60 (40–88) months]. A flow-chart summarizing CAD diagnosis over time is depicted in Figure 1. Overall, 119 (36.7%) patients had CAD evaluation prior to KT, of whom 21 underwent myocardial revascularization – 8, 12 and 1 patients with acute coronary syndrome (ACS), chronic coronary syndrome (CCS) and silent ischaemia, respectively. At a median time of 46 (25–66) months after KT, 36 (11.1%) more patients had CAD evaluation, of whom 8 underwent percutaneous myocardial revascularization – 6 and 2 for ACS and CCS, respectively. Those with obstructive CAD were older (64 vs 54 years-old; p<0.001), with a higher burden of cardiovascular (CV) risk factors (p<0.001) and more likely to have had a CV death (9.5 vs. 1.0%; p=0.025) or CV hospitalization (38.1 vs. 13.4%; p=0.007). CAD status (revascularized vs. non-revascularized) was not associated with improved major outcomes at follow-up. We found no strong predictors of CAD requiring revascularization post-KT, including time from RRT to KT. There were no patients with refractory angina, left main disease or reduced left ventricular ejection fraction (<40%) in need of myocardial revascularization over follow-up. Conclusions: Obstructive CAD was uncommon in our cohort of patients who received a KT, most of whom with asymptomatic or mildly (monthly angina) symptomatic CCS or non-fatal ACS. These findings, together with the most recent evidence, may argue against routine CAD screening in all patients being enlisted for KT. Notwithstanding, randomized evidence is eagerly awaited to further guide treatment decisions in the post-ISCHEMIA-CKD era. Funding Acknowledgement: Type of funding sources: None.